1. Trang chủ
  2. » Giáo án - Bài giảng

BOUNDARY VALUE OF PROLEMS DIFFERENTIAL EQUATIONS

17 130 0

Đang tải... (xem toàn văn)

Tài liệu hạn chế xem trước, để xem đầy đủ mời bạn chọn Tải xuống

THÔNG TIN TÀI LIỆU

Thông tin cơ bản

Định dạng
Số trang 17
Dung lượng 112,65 KB

Nội dung

WEBSITE : http://maths-minhthe.violet.vn BOUNDARY VALUE PROBLEMS OF DIFFERENTIAL EQUATIONS (5390) The Minh Tran 1. Solution a) Because '' u (x) 1 = , so we have the genaral form of u(x) : ( ) 2 x u x ax b 2 = + + ' ' From the condition boundary : u(0) 2u (0) 1 ; u(1) 0 We have 2a b 1 3 a u(0) 2u (0) 1 2 1 a b u(1) 0 b 2 2 + = = + =    = + =   ⇔ ⇔    + = − =    = −   Thus, ( ) 2 x 3 u x x 2 2 2 = + − b) Solution : We have the equation : ( ) ( ) ( ) 1 N 0 u x G x, f d u (x) = ξ ξ ξ + ∫ We see that 2 2 1 N N N N N 1 d u Lu f and has two extra boundary conditions,so dx u L f u where u has to be in the null space of L We compute L to both sides of the equation so Lu f since Lu 0, u is det er mined by the boundary co ndition and u 2(1 x) Hence, u L f u − − = = = + = = = − − = + N 1 0 1 1 2 2 0 0 write out as: G(x, )f( )d 2(1 x) , compute L to this expression : d L G(x, )f( )d LG(x, )f( )d f(x), where L dx ξ ξ ξ− − ξ ξ ξ = ξ ξ ξ = = ∫ ∫ ∫ From the condition boundary, the Green’s function G(x, ) ξ satisfies : 2 ' 2 d G(x, ) (x ) , G(1, ) 0 , G(0, ) 2G (0, ) 1 dx ξ = δ − ξ ξ = ξ + ξ = We have ( ) a bx , x G x, c dx , x + < ξ  ξ =  + > ξ  The constant a, b,c,d are different Where x < ξ : ' G(0, ) 2G (0, ) 1 a 2b 1 a 1 2b ξ + ξ = ⇒ + = ⇒ = − Where x > ξ : G(1, ) 0 c d 0 c d ξ = ⇒ + = ⇒ = − Hence, ( ) 1 2b bx ,x (1) G x, d dx ,x − + < ξ  ξ =  − + > ξ  We continue to check at x = ξ ( ) ( ) ( ) (2) G , G , Derivativing of G x, from x to x dG dG (3) 1 dx dx x x From (1) and (2) we have : 1 2b b d d From (2) and (3) we have : d b 1 − + − + + − ξ ξ = ξ ξ ξ = ξ = ξ − = = ξ = ξ − + ξ = − + ξ − = Soving the equation system 1 2b b d d b 2 d b 1 d 3 − + ξ = − + ξ = − ξ   ⇒   − = = − ξ   ( ) ( )( ) ( )( ) Thus 1 2 x 2 ,x G x, 3 1 x ,x  − − ξ − < ξ  ξ =  − ξ − > ξ   The representation : ( ) ( ) ( ) 1 0 u x G x, f d 2(1 x) = ξ ξ ξ − − ∫ c) We have the equation : ( ) ( ) ( ) = ξ ξ ξ ∫ 1 0 u x G x, f d with 0 1 x < < We have the condition boundary : , ( ) ' ' ' 3 3 u (x) x u (0) u(0) 2u (0) 1 2 2 u(0) 2 1 3 u 1 2 0 2 2 = + ⇒ = ⇒ + = = − = α ⇒ = + − = = β We have the genarally form of u(x) : ( ) ( ) ( ) ( ) = ξ ξ ξ + β + α − ∫ 1 0 u x G x, f d x 1 x We have the function ( ) , G x ξ as the formula below : ( ) ( ) ( ) ( )( ) 1 2 x 2 ,x G x, 3 1 x ,x  − − ξ − < ξ  ξ =  − ξ − > ξ   ( ) ( ) '' 1 , 1 = = with u x f ξ ( ) ( ) ( ) ( ) ( ) ( ) ( ) ( ) ( ) ( )( ) ( ) ( )( ) ( ) ( ) ( ) ( ) ( ) ( ) 1 0 x 1 0 x x 1 0 x 2 2 2 2 2 u x G x, f d x 1 x G x, f d G x, f d 2 1 x 1 2 x 2 d 3 1 x d 2 1 x x 1 2 x 2 3 1 x 2 1 x 2 0 2 x x 1 x x 2x x 2 (1 x) (3 ) (3x ) 2 1 x 2 2 2 x 3 1 x 2 2 2 = ξ ξ ξ + β + α − = ξ ξ ξ + ξ ξ ξ − − = − − ξ − ξ + − ξ − ξ − −       ξ ξ = ξ − ξ − − + ξ − − − −                   = − − − + − − − − − −             = + + ∫ ∫ ∫ ∫ ∫ Thus, ( ) 2 x 3 1 u x x 2 2 2 = + + We see two solutions from the above are the same 2. ( ) ( ) ( ) ( ) ( ) ( ) 2 2 2 2 u u a ) sin5x t x We assum that u(x,t) x G t where x is only a function of x and G t is a function of t We will get firstpartial derivetive of u(x,t) w ith respect to t and the fourth partial derivative with respect to x dG t u x t dt u x ∂ ∂ = + ∂ ∂ = φ φ ∂ = φ ∂ ∂ = ∂ ( ) ( ) 2 2 2 2 d G(t) dx dG t d x G(t) (1) dt dx φ φ ⇒ φ = ( ) ( ) 2 2 We can separate var iableby dividing both sides of (1) by x G(t) dG t 1 1 d sin5x G dt dx G We can not solve by the method of separation of var iables because the presence of a terms like sin5x is forbidden φ φ = + φ φ " 2 n n n n 1 ' t n n n 1 2 xx n n n 1 b) We have 0 We have the boundary condition (0) ( ) 0 2 and have the solution is (x) sinnx , n u(x,t) B (t) u (x,t) B (t) u (x,t) n B (t) ∞ = ∞ = ∞ = φ + λφ = φ = φ π = φ = λ = π ⇒ = φ ⇒ = φ ⇒ = − φ ∑ ∑ ∑ n n n 1 5 n n n 1 n Set q(x,t) sin5x C (t) 2 q(x,t) can written as q(x,t) (x) comparing with q(x,t) sin5x C (t) 2 n 5 We see that C (t) 0 n 5 ∞ = ∞ = = = φ = φ π = = φ  =  = π   ≠  ∑ ∑ The initial condition is 1 2 u(x,0) 0 sin0 (x) = = = φ π The fourier expantion is n n 0 n 1 n 2 u(x,0) B (0) (x) 0 (x) 2 n 0 B (0) 0 n 0 ∞ = = φ = = φ π  =  = π   ≠  ∑ t xx ' 2 n n n n n n n 1 n 1 n 1 ' 2 n n n ' 2 5 n n n From the equation u u sin5x and the formula from t he above B (t) n B (t) C (t) The differential equation : B (t) n B (t) C (t) We can solve : 2 C , n 5 B (t) n B (t) 0 ,n 5 2 n 0 with B (0) ∞ ∞ ∞ = = = = + ⇒ φ = − φ + φ ⇒ + =  = =  + = π   ≠  = = π ∑ ∑ ∑ 0 n 0     ≠  ' 0 0 0 Case 1: n 0 B (0) 0 2 B (0) 2 B (0) =  =  ⇒ =  π =  π  ( ) ' 25t 25t 5 5 5 5 Case 2 : n 5 2 B (t) 25B (t) 1 2 B (t) e e 1 25 B (0) 0 − =  + =  ⇒ = − π  π  =  ' 2 n n n n Case 3: n 5 and n 0 B (t) n B (t) 0 B (0) 0 B (t) 0 ≠ ≠  + =   =   ⇒ = ( ) n n n 1 25t 25t Finally ,the solution is : u(x,t) B (t) 1 2 2 u(x,t) e e 1 sin5x 25 ∞ = − = φ ⇒ = − π π ∑ 3. Solve the following two types of problems : ( ) ( ) " ' ' a) u u subject to u 0 0 u 1 − = λ = = We have the equation form : ( ) ( ) ( ) " 2 2 2 sx sx 2s 0 We have the auxiliary equation : r 0 (*) Case 1 : 0 (*) r 0 r 0 r s x Ae Be d 0 0 A B dx A B 0 and so d A Be 1 0 dx There are no − − φ + λφ = + λ = λ < ⇔ + λ = ⇔ = −λ > ⇔ = ± −λ = ± ⇒ φ = + φ  =  =   ⇔ ⇔ = =   φ =   =   λ ( ) ( ) ( ) ( ) 2 1 2 Case 2 : 0 (*) r 0 r r 0 x A Bx d 0 0 dx A 0; B 0 and so dim 1 d 1 0 dx x A const is an eigenfunction λ = ⇔ = ⇔ = = ⇒ φ = + φ  =   ⇔ ≠ = =  φ  =   φ = = ( ) ( ) ( ) ( ) 2 2 2 2 Case 3 : 0 (*) r 0 r 0 r i x A cos x Bsin x d 0 0 dx sin 0 d 1 0 dx n n n when n 0 dim 2 λ > ⇔ + λ = ⇔ = −λ < ⇒ = ± λ ⇒ φ = λ + λ φ  =   ⇔ λ =  φ  =   ⇔ λ = π ∈ ⇒ λ = π > ⇒ = » ( ) ( ) " ' ' b) u u subject to u 0 0 ; u 1 1 − = λ = = We have the equation form : ( ) ( ) ( ) " 2 2 2 sx sx s 2s sx sx 0 We have the auxiliary equation : r 0 (*) Case 1 : 0 (*) r 0 r 0 r s x Ae Be d 0 0 e dx A B where s 0 and so s(e 1)d 1 1 dx When 0 the solution is Ae Be ,where A,B is the same as the a − − − φ + λφ = + λ = λ < ⇔ + λ = ⇔ = −λ > ⇔ = ± −λ = ± ⇒ φ = + φ  =   ⇔ = = = −λ >  −φ  =   λ < + bove ( ) ( ) ( ) 2 1 2 Case 2 : 0 (*) r 0 r r 0 x A Bx d 0 0 A 0; B 0 dx d 1 1 A 0; B 1 dx There is no 0 λ = ⇔ = ⇔ = = ⇒ φ = + φ  = ⇒ ≠ =    φ  = ⇒ ≠ =   λ = ( ) ( ) ( ) ( ) 2 2 Case 3 : 0 (*) r 0 r 0 r i x A cos x B sin x d 0 0 B 0 B 0 dx d 1 1 A sin 1 dx 1 A sin 1 x A cos x cos x sin 1 When 0 the solution is cos x sin λ > ⇔ + λ = ⇔ = −λ < ⇒ = ± λ ⇒ φ = λ + λ φ  = ⇔ λ = ⇒ =    φ  = ⇔ − λ λ =   − = λ λ − ⇒ φ = λ = λ λ λ − λ > λ λ λ Condition : The problem a) is an eigenvalue prolem ( ) ( ) ( ) ( ) ( ) ( ) ( ) ( ) ( ) i kx t tt xx 2 i kx t tt 2 i kx t xx tt xx 2 2 i kx t i kx t 2 2 1 tt xx 2 1 2 4. We have u(x,t) e and u cu u i e u ki e u cu i e c ki e ck k c Re turn the problem which is given c for x 0 We see that u cu where c(x) c for x 0 k c for x 0 k c for x −ω −ω −ω −ω −ω = = ⇒ = ω ⇒ = ⇒ = ⇔ ω = ⇔ ω = ⇒ ω = <  = =  >  < ω = > ( ) i kx t ikx ikx t 0 u(x,t) e u(x,0) e f(x) u (x,0) ( i)e g(x) −ω      = ⇒ = = ⇒ = −ω = ( ) ( ) 1 1 x ikx ikx ikx ikx 1 1 0 x ikx ikx ikx ikx 1 1 0 For x 0 u(x,t) F(x c t) G(x c t) 1 1 1 1 F(x) e ( i)e dx e 1 e 2 2c 2 2c k 1 1 1 1 G(x) e ( i)e dx e 1 e 2 2c 2 2c k < = − + + ω = − −ω = − − ω = + −ω = + − ∫ ∫ ( ) 1 1 1 1 1 1 tki c it 1 1 1 1 1 1 1 1 x ik c ( t ) ik( x c t ) c ik( x If x c t , u(x,t) f(x c t) x c t ,we have u(0,t) h(t) e e h(t) u(0,t) F( c t) G(c t) z z and h( ) F( z) G(z) G(z) h( ) F( z) ; z 0 c c x Thus, u(x,t) f(x c t) h( t) f (x c t) c e e e − −ω − + − − + < = − > = = = = = − + = − + ⇒ = − − > = − + + − − + = + − 1 c t) ( ) ( ) 2 2 x ikx ikx ikx ikx 1 1 0 x ikx ikx ikx ikx 1 1 0 2 2 2 2 2 For x 0 u(x,t) Q(x c t) P(x c t) 1 1 1 1 Q(x) e ( i)e dx e 1 e 2 2c 2 2c k 1 1 1 1 G(x) e ( i)e dx e 1 e 2 2c 2 2c k x c t : h(t) Q( c t) P(c t) where x 0 z Q(z) h( ) P( z) , z 0 c x u(x,t) h(t c > = − + + ω = − −ω = − − ω = + −ω = + − < = − + = − ⇒ = − − < = − ∫ ∫ 2 x i t c ) e   −ω −     = ( ) ( ) x x x ' ' ' ' 1 1 1 1 2 2 ' ' ' ' 1 1 1 2 2 1 1 2 We continue to use the continuity of u at x 0 u (0 ,t) u (0 ,t) 1 x 1 x f (x c t) h ( t) f (x c t) h (t ) c c c c Setting x 0 we have 1 1 f ( c t) h (t) f c t h (t) c c 2c f( c t) h(t) c c + − = =   − + + + − + = − −     =   − + + − = −     − ⇒ = + [...]... − x = 1 dt 2t dt 2t Multiplying e 1 − ln t 2 in two sides of the equation 1 − ln t 2 1 − ln t  dx s2 1  − x = e 2  dt 2t   1 1 1 − ln t dx − ln t 1 − ln t s2 e 2 −e 2 x=e 2 dt 2t 1 1 − ln t dx s2  − 2 ln t  e x s2  = e 2  dt   e − 1 − 1 t 2 x s2 = ∫ t 2 dt − 1 2 1 2 t x s2 = 2t + c ⇒ x s2 = 2t + c t We have int er sec tion of the equations : 4t = 3t + 1 ⇒ t = 1 with t = 1 then 3t + 1 = 2t... see that c = t Usin g the method of characteristics dx t2 t2 = −t ⇒ x = − + x0 ⇒ x 0 = x + dt 2 2 Generally, we have two cases dω If ω = 0 , =0 dt t2 ω(x,t) = p(x 0 ) = p(x + ) with ω(x,0) = p(x) = f(x) 2 2 t Thus, ω(x,t) = f(x + ) 2 dω ∂ω ∂ω = −t =ω If ω ≠ 0 then ∂t ∂x dt t2 When x 0 = x + > 0 2 2 t ⇒x>− 2 dω = ω ⇒ ω(x,t) = ω0 (x 0 ,t)et where ω0 (x 0 ,t) is the value of ω(x,t) at t = 0 dt t2 From the... 0 ) = f(x + ) 2 2 t Thus, ω(x,t) = f(x + )e t 2 When x 0 = x + ⇒x . http://maths-minhthe.violet.vn BOUNDARY VALUE PROBLEMS OF DIFFERENTIAL EQUATIONS (5390) The Minh Tran 1. Solution a) Because '' u (x) 1 = , so we have the genaral form of u(x) :. has two extra boundary conditions,so dx u L f u where u has to be in the null space of L We compute L to both sides of the equation so Lu f since Lu 0, u is det er mined by the boundary co ndition. separate var iableby dividing both sides of (1) by x G(t) dG t 1 1 d sin5x G dt dx G We can not solve by the method of separation of var iables because the presence of a terms like sin5x is forbidden φ φ =

Ngày đăng: 02/11/2014, 13:00

w